Prognostic Significance of Claudin-4 in Relation to Key Tumor Budding and Invasion Parameters in Colorectal Adenocarcinoma - Puspitasari, Ririn Endah; Miskad, Upik Andriani; Cangara, Muhammad Husni; Wahid, Syarifuddin; Achmad, Djumadi; Yamin, Amalia; Tawali, Suryani (Asian Pacific Journal of Cancer Biology, 2026)
Objective: Colorectal cancer (CRC) is a major global health burden. Claudin-4, a tight junction protein preserving epithelial cohesion, has paradoxically been implicated in tumor progression. Its prognostic role in CRC remains unclear, particularly regarding histopathological grade, tumor budding, tumor-infiltrating lymphocytes (TILs), and deep invasion. This study aimed to clarify these associations. Methods: This cross-sectional study included 95 formalin-fixed, paraffin-embedded colorectal adenocarcinoma specimens obtained from 2022 to 2024. Claudin-4 expression was assessed immunohistochemically using the TIS. Tumor budding was evaluated according to ITBCC 2016, TILs based on ITWG criteria, histopathological grade using the WHO classification, and deep invasion (pT1–pT3) based on the AJCC 8th edition. Statistical analysis was performed with Chi-square, Mann–Whitney, and Kruskal–Wallis tests. Results: Strong Claudin-4 expression was found in 47.4% of cases. Expression correlated significantly with tumor budding (p = 0.038) and deep invasion (p = 0.038), but not with histopathological grade (p = 0.113) or TILs (p = 0.170). Mean TIS values showed a non-significant upward trend with grade and TIL density. Conclusion: Claudin-4 is significantly associated with markers of invasiveness, supporting its value as a prognostic biomarker of tumor aggressiveness in colorectal adenocarcinoma.